1960
DOI: 10.1121/1.1908276
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Temporal Auditory Summation

Abstract: A theory of temporal auditory summation is developed and applied to the threshold of audibility for various temporal patterns of pulses and sinusoidal vibrations. The theory is based on the assumption of an exponential decay of neural excitation and, for the threshold of audibility, it includes only one time constant. Various factors that may affect temporal auditory summation are discussed. It is shown that the same theory applies to muscle contractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
141
1
3

Year Published

1974
1974
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(156 citation statements)
references
References 0 publications
11
141
1
3
Order By: Relevance
“…5 is the predicted results from Zwislocki's [30] theory of temporal neural integration. In this model, the magnitude of the neural response increases over time of stimulation and when it exceeds threshold level, a detection response is made by the observer.…”
Section: Temporal and Spatial Summationmentioning
confidence: 92%
“…5 is the predicted results from Zwislocki's [30] theory of temporal neural integration. In this model, the magnitude of the neural response increases over time of stimulation and when it exceeds threshold level, a detection response is made by the observer.…”
Section: Temporal and Spatial Summationmentioning
confidence: 92%
“…Similarly, Florentine et al (1988) thoroughly tested and rejected the idea that the reduced slope may be due to the higher SPLs of the stimuli needed to reach absolute threshold in hearing-impaired listeners, and they concluded that it reflects reduced temporal integration per se. Saunders et al (1995), in following the idea that the integrator may be located centrally (e.g., Zwislocki 1960), have suggested that the neural integrator exhibits considerable plasticity since a normal slope of the temporal integration function can be restored in the chicken when damaged structures in the avian cochlea regenerate. However, there is no need to assume such plasticity if the integrator is located very peripherally, as suggested by us (Heil and Neubauer 2003).…”
Section: Location Of Damages Captured By Altered Baseline and Gainmentioning
confidence: 99%
“…This trading relationship, sometimes called temporal integration function, is frequently interpreted to indicate that the auditory system integrates sound over time. Until recently, the prevailing view has been that the sound quantity ultimately integrated by the auditory system is sound intensity and that consequently absolute thresholds are best defined in terms of acoustic energy density (Garner 1947;Feldtkeller and Oetinger 1956;Plomp and Bouman 1959;Zwislocki 1960 However, there has been no consensus as to where the integrator may be located nor as to how it may operate. For example, it is unclear whether an integration process in the literal or physical sense exists at all and whether it is a deterministic or rather a probabilistic process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal detection performance of human and animal observers benefits from repetitive activation at perceptual threshold in several sensory systems ["temporal summation"; audition: Heil and Neubauer (2003); Zwislocki (1960); touch : Gescheider et al (1999); Verrillo (1965)]. The neural processes underlying this phenomenon must involve some sort of temporal integration of incoming signals.…”
Section: Introductionmentioning
confidence: 99%